Penerapan Layanan Bimbingan Kelompok Dalam Mengembangkan Konsep Diri Pada Siswa Kelas VIII MTS AR RIDHA - Nurjannah Salsabila Simanungkalit; Uli Makmun Hasibuan; Reva Lina Aulia; Arzela Azrina (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Adolescence is a crucial phase in the formation of self-concept, which influences students' self-confidence and learning motivation. This study aims to describe the implementation of group guidance services in developing the self-concept of eighth-grade students at MTs Ar-Ridha. The research method used was descriptive qualitative. The research subjects consisted of 5 eighth-grade students who participated in a 25-minute group guidance session on the topic of "Self-Concept". The implementation methods included group discussions, question-and-answer sessions, experience sharing, and ice-breaking activities supported by PowerPoint media. Data were collected through direct process and product evaluations. The process evaluation results showed that the group dynamics were conducive, with students participating actively, orderly, and respectfully toward each other's opinions. The product evaluation indicated an increase in students' understanding of recognizing their strengths and weaknesses, fostering a positive mindset, and enhancing motivation and self-confidence. This study concludes that the implementation of group guidance services is effective in helping eighth-grade students at MTs Ar-Ridha form a healthier and more positive self-concept.